Factors Associated with Pregnancy Hypertension Risk - Sinambela, Megawati; Hardisman, Hardisman; Yusrawati, Yusrawati; Bachtiar, Adang; Masrul, Masrul; Mudjiran, Mudjiran; Malini, Hema; Defrin, Defrin (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
Background: Hypertension in pregnancy needs to beware out because it can progress to more severe conditions, namely preeclampsia and eclampsia, thereby endangering the mother and the unborn baby. Risk factors in Hypertension in pregnancy are as age, education, occupation, parity, gestational age, economic factors, personal and family history of hypertension, obesity and activity/exercise.Objective: This study aims to determine the risk factors for Hypertension in pregnancy in Deli Serdang Regency, North Sumatra.Method: This study method used analytic observational with a cross sectional design. The study subjects were pregnant women at Public Health Center of Deli Serdang Regency who were considered the inclusion criteria and were selected as study subjects. The sampling technique by means of random sampling amounted to 164. Univariate analysis used to get an overview of the frequency distribution and percentage of the variables to be studied. Bivariate analysis used to determine the relationship between the independent variable and the dependent variable. The statistical test was Chi-Square with CI 95%.  If p < 0.05. Multivariate analysis with logistic regression statistical tests to determine the influence of the independent variables on the dependent variable. Independent variables with p value <0.25 were included in the multiple logistic regression test model and selected using the enter method. The strength of the influence of the independent variable on the dependent variable is the Exp value (ß).Result: The results of the study proved the results of Multivariate analysis, can be synthesized that the risk factors for pregnancy hypertension were influenced by factors: education (p=0.045), parity (p=0.047), gestational age (0p=0.040), personal history of hypertension (p=0.013), history family (p=0.049), and obesity (p=0.016). While the factors of age, occupation, economy and activity/exercise have no effect on risk factors for hypertension in pregnancy. Based on Exp value (B), the most influential factor was personal history of hypertension (p=0.013). This is indicated by the Exp value (B) = 2.710 which is in the interval 1.234 – 5.953, followed by obesity (p=0.016) with the Exp value (= 2.612) which is in the interval 1.192 – 5.725.